Psychometric validation of the Farsi Bergen social media addiction scale (BSMAS) among Iranian adults - Saeid Sadeghi; Bita Shalani; Seyed Mahdi Firouzabadi; Zahra Babaei; Sara Arian Namazi; Hamid Reza Pouretemad (BMC Public Health)
Abstract This study investigated the psychometric characteristics of the Bergen Social Media Addiction Scale (BSMAS) in a sample of Iranian adults aged between 19 and 73 years. In a cross-sectional study carried out between September 2023 and November 2023, 1044 participants (753 female and 291 male) were selected using a convenience sampling method to examine the relationship between BSMAS, Young’s internet addiction (YIA), and mental health. Participants completed several questionnaires, including the BSMAS, YIA scale, and Depression Anxiety and Stress Scale (DASS-21). The BSMAS validity and reliability were evaluated using construct validity, reliability, and concurrent validity. Confirmatory factor analysis demonstrated good model fit (e.g., CFI = 0.94), with all items loading significantly. Additionally, the Cronbach’s alpha coefficient (0.795), the Guttman’s split-half coefficient (0.735), and the McDonald’s omega coefficient (0.797) indicate acceptable reliability for the BSMAS. Significant positive relationships were found between the BSMAS and YIA (r = 0.64, p 0.01), depression (r = 0.32, p < 0.01), anxiety (r = 0.32, p < 0.01), and stress (r = 0.37, p < 0.01). We found that females scored higher on the Bergen than males. A negative correlation was also found between the Bergen score and age among all participants. The results suggest that the concurrent validity of the BSMAS is acceptable. In conclusion, the BSMAS is a valid and reliable scale for assessing social media addiction (SMA) evaluations in Iranian populations.